(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2018)
This work presents design, instrumented and test of a parabolic trough solar collectorunder Baghdad climate conditions (of latitude 33.33o N, of longitude 44.4oE). The parabolictrough solar collector consists of: a mirror matrix or tapes which work as reflective surfaceof (2m *1m), absorber copper tube (receiver), two axis tracking system. Water is used as aheat transfer medium. The setup is tested within clear days from June, to September 2017.The collector heat gain, efficacy and temperature of absorber were presented for absorberfive different circulating mass flow rates of (0.15, 0.2, 0.3, 0.4, 0.5) 1pm. The results showthat the maximum thermal efficiency of the parabolic trough solar collector is 80.26%. Themaximum outlet temperature of the absorber tube reaches 81 oC at the noon when waterflows at (0.15) 1pm. The maximum obtained heat gain is (1619W) for (0.5) 1pm flow rate ofwater.